Frequent expression of PD‐L1 on circulating breast cancer cells. Issue 9 (9th June 2015) - Mazel, Martine; Jacot, William; Pantel, Klaus; Bartkowiak, Kai; Topart, Delphine; Cayrefourcq, Laure; Rossille, Delphine; Maudelonde, Thierry; Fest, Thierry; Alix-Panabières, Catherine
Abstract : Immune checkpoint regulators such as PD‐L1 have become exciting new therapeutic targets leading to long lasting remissions in patients with advanced malignancies. However, in view of the remarkable costs and the toxicity profiles of these therapies, predictive biomarkers able to discriminate responders from non‐responders are urgently needed. In the present paper, we provide evidence that PD‐L1 is frequently expressed on metastatic cells circulating in the blood of hormone receptor‐positive, HER2‐negative breast cancer patients. We performed western blot, flow cytometry and immunocytochemical analyses to demonstrate the specificity of the PDL1 antibody used in our study and established immunoscores for PDL1 expression on single tumor cells. We then selected sixteen patients with circulating tumor cells (CTCs) using the CellSearch® system and found PD‐L1(+) CTCs in 11 patients (68.8%). The fraction of PD‐L1(+) CTCs varied from 0.2 to 100% in individual patients. This is the first report demonstrating the expression of PD‐L1 on CTCs. The established CTC/PD‐L1 assay can be used for liquid biopsy in future clinical trials for stratification and monitoring of cancer patients undergoing immune checkpoint blockade. Highlights: PD‐L1 is an immune checkpoint regulator. PD‐L1 is frequently expressed on metastatic cells circulating in the blood of breast cancer patients. We report an established CTC/PD‐L1 assay that can be used for liquid biopsy in cancer patients. Detection of PD‐L1(+) CTCs may guide stratification and monitoring of cancer patients undergoing immune checkpoint blockade.